Rotavirus Gastroenteritis in a Neonatal Unit of a Greek Tertiary Hospital: Clinical Characteristics and Genotypes - Koukou, Dimitra (PLoS One, 2015)
INTRODUCTION: Rotavirus (RV) infection in neonatal age can be mild or even asymptomatic. Several studies have reported that RV is responsible for 31%-87% of pediatric nosocomial diarrhea and causes gastroenteritis outbreaks in pediatric and neonatal units. OBJECTIVES: Study clinical characteristics, genotypes and risk factors of RV infection in neonatal age. METHODS: A prospective study was conducted from April 2009 till April 2013 in the neonatal special care unit of the largest tertiary pediatric hospital of Greece. Fecal samples and epidemiological data were collected from each neonate with gastrointestinal symptoms. RV antigen was detected with a rapid immunochromatography test. RV positive samples were further genotyped with RT PCR and sequencing using specific VP7 and VP4 primers. RESULTS: Positive for RV were 126/415 samples (30.4%). Mean age of onset was 18 days. Seventy four cases (58%) were hospital acquired. Seasonality of RV infection did not differ significantly throughout the year with the exception of 4 outbreaks. Genotypes found during the study period were G4P[8] (58.7%), G1P[8] (14.7%), G12P[8] (9.3%), G3P[8] (9.3%), G12P[6] (5.3%), G9P[8] (1.3%) and G2P[4] (1.3%). RV cases presented with: diarrhea (81%), vomiting (26.2%), fever (34.9%), dehydration (28.6%), feeding intolerance (39.7%), weight loss (54%), whilst 19% of cases were asymptomatic. Comparing community with hospital acquired cases differences in clinical manifestations were found. CONCLUSIONS: Significant incidence of nosocomially transmitted RV infection in neonatal age including asymptomatic illness exists. Genotypes causing nosocomial outbreaks are not different from community strains. Circulating vaccines can be effective in prevention of nosocomial RV infection through herd immunity.